Analisis Arah dan Kecepatan Angin Permukaan untuk Operasional Penerbangan di Bandara Internasional Zainuddin Abdul Madjid - Primadi, Topan Satria; Dewita, Anggi; Zulaichah, Nur Siti; Dewi, Aprilia Mustika (Buletin GAW Bariri (BGB), 2025)
Zainuddin Abdul Madjid International Airport (BIZAM), located on Lombok Island, serves both international and domestic flight operations. In aviation, wind effects are categorized as headwind, tailwind, and crosswind. However, tailwind and crosswind with significant speeds are generally considered hazardous to flights. This research aims to analyze surface wind direction and speed patterns at BIZAM to identify potential flight risks associated with tailwind and crosswind phenomena and provide appropriate mitigation recommendations. The study employed windrose diagrams and statistical methods, using 10 years of surface wind direction and speed data (2014–2023) obtained from synoptic observations at the Class II Zainuddin Abdul Madjid Meteorological Station. Findings indicate that wind patterns in the BIZAM area are influenced by monsoon wind movements, with peak wind speeds exceeding ≥21.58 knots. A significant temporal shift in wind dominance was observed: westerly winds (from the west to southwest sector) are now dominant not only from December to February but also extend into March. Conversely, the dominance of winds from the southeast sector begins earlier, in April, and persists until December, reflecting the Australian Monsoon's earlier onset and longer duration than usual. The highest incidence of crosswind events with speeds >13 knots was recorded in December, accounting for 0.15%. Assuming aircraft are landing on Runway 31, pilots are recommended to use this runway in January, February, March, and December, as the percentage of tailwind during these months is lower than the percentage of headwind. Given the potential hazards posed by crosswind and tailwind events, pilots and flight operators are advised to exercise caution when flying during these months.